Insight on Theoretical and Conceptual Review on the Diffusion of Innovative Marketing Digital Transformation Systems in Circular Economy Era - Julius Jillbert; Andi Nur Baumassepe; Amaluddin Fatih Ghurron; Valentino Aris (IECON: International Economics and Business Conference, 2023)
This article is related to the diffusion of innovations, especially those known based on the Innovation Diffusion Theory or IDT which states that in general diffusion behaviour can be defined through individual perceptions regarding the use of certain innovations. The basic definition of diffusion gives rise to different understandings in two research streams. First, in economics and non-marketing disciplines, diffusion is seen as the spread of an innovation over time among different groups (Brown, 1981). While the second in the marketing discipline, diffusion refers to "the process of an innovation being communicated through certain channels over time to members of a social system" (Rogers, 2003,pp. 110-119). This article closes with suggestions for a more comprehensive innovation marketing system based on the framework of digital transformation that not only would be useful for the future researcher, but also for the real- world domain as it begins with people his/herself, the marketing process, and marketing application in real-world business practice as it gives them an advantage over their competitors to strive during the age of circular economy.